ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN WRITING FOLKLORE - Tiara Widyaiswara; Moh Nurman; Luthfiyati, Dian; Firda Safira Andini (Jurnal Muara Pendidikan, 2025)
The ability to write narrative texts in English is still a challenge for many high school students. Folklore is chosen as a learning medium because it contains cultural elements and a distinctive narrative structure. This study aims to analyze grammatical errors in writing folklore texts by class 10E students of SMA Negeri 1 Sukodadi and identify the factors that cause difficulties. This study uses a qualitative approach with a descriptive method. Data were obtained through written tests and structured interviews. Of the 30 students, 20 writings that met the criteria were analyzed, consisting of 10 long writings (more than two sentences) and 10 short writings (less than two sentences). Data analysis was carried out by identifying, grouping, and interpreting errors based on the surface strategy taxonomy of Dulay, Burt, and Krashen (1982), which includes omission, addition, misformation, and misordering. The results showed that the most dominant error was misformation (57,43%), followed by omission (25,68%), addition ( 8,78% and misordering each at (8,11%). Difficulties faced students include limitations in grammar and vocabulary, the influence of the mother tongue, lack of understanding of narrative structure, and low self-confidence and revision skills.